2013
DOI: 10.3109/21691401.2013.768627
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of magnetically responsive albumin nanospheres andin vitrodrug release studies

Abstract: In this work, doxorubicin (DOX)-loaded magnetic albumin nanospheres were prepared using desolvation method in order to develop magnetically responsive nanocarrier system. Nanoparticles were characterized with zetasizer, SEM, AFM, XRD and magnetometer. In vitro DOX release was also investigated. It was found that nanoparticles had spherical shape with narrow size distributions and had magnetic responsiveness. In addition, slower drug release was observed with nanoparticulate system compared with free DOX. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…Cellular uptake of nanoparticles and large molecules is generally accepted to be by an endocytosis mechanism through which they accumulate in the acidic compartments of early endosomes and then trafficked to the lysosomes . As we showed in the earlier study , DOX release from nanoparticles in acidic medium is faster. Therefore, we can suggest that after nanoparticles internalized into cells, DOX released from nanoparticles in the acidic intracellular organelles.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Cellular uptake of nanoparticles and large molecules is generally accepted to be by an endocytosis mechanism through which they accumulate in the acidic compartments of early endosomes and then trafficked to the lysosomes . As we showed in the earlier study , DOX release from nanoparticles in acidic medium is faster. Therefore, we can suggest that after nanoparticles internalized into cells, DOX released from nanoparticles in the acidic intracellular organelles.…”
Section: Resultssupporting
confidence: 64%
“…Magnetization value of M-DOX-BSA-NPs was found experimentally 2.5 emu/g at room temperature when 500 G of magnetic field was applied. XRD pattern analysis also has confirmed Fe 3 O 4 structure in albumin nanoparticles (5). These data have demonstrated that M-DOX-BSA-NPs are responsive to the magnetic field and have ideal properties as a drug carrier.…”
Section: Resultssupporting
confidence: 54%
“…Albumin at F has an increased viscosity and decreased dissolvability, 26 which aids its formation into nanospheres. Transmission electron microscopy ( Figure 1) showed FA-DOX-BSA MNPs to be approximately round in shape, and this has also been demonstrated by Ak et al 27 and Shen et al 28 The particles were uniform in size. Moreover, an Fe 3 O 4 area in the particle center could be seen in all particles.…”
mentioning
confidence: 56%
“…Albumin is another commonly used and clinically relevant stabilizing agent seen in various drug nanoparticle or drug formulations. In a single step, magnetic nanoparticles decorated by albumin, which is cross-linked using glutaraldehyde, were suitable for providing a uniform nanoparticle system for prostate cancer [24,30]. Similarly, liposome [15,31,32], hybrid [33], and dual/multilayer can serve as layers for stable nanoformulations.…”
Section: Magnetic Nanoparticlesmentioning
confidence: 99%